Sustainable Lighting for High-Rise Buildings: Lighting Solutions for High-Rise Buildings in the Context of Sustainability - Becker, Jonas J (Journal of A Sustainable Global South; Vol 3 No 2 (2019): August 2019, 2019)
As awareness about Human Centric Lighting rises sustainable lighting concepts in high-rise architecture are more and more considered. Health and wellbeing are terms that become an essential part in light planning. The question is if there are sustainable solutions to improve this problem and if so how to implement them in the lighting planning of a modern high-rise building properly? And is there potential for improvement in sustainability of lighting solutions when it comes to working or living conditions? Two main sources of light are looked at: Daylight and artificial lighting. In the case of a modern high-rise building the lighting design necessarily consists of them both. However, the conclusions of the researches looked at in this paper show that it is of utmost importance of how this technology is applied. My findings show that melanopic effective lighting has the power to coordinate our circadian rhythms. Lighting solutions for daytime can positively influence our circadian rhythm by the consideration of natural light in project planning as well as the use of intelligent artificial lighting solutions such as the ones done research on. Keywords : sustainable lighting, human centric lighting, high rise building